Makna Bahasa Figuratif pada Lirik Lagu Kiss From A Rose Oleh Seal - I Gusti Ayu I Gusti Ayu Nila Wijayanti (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2018)
Figurative language is language that uses words or expressions with a meaning that is different from literal interpretation. When a writer uses literal language, he or she is simply stating the facts as they are. Figurative language is very common in poetry, but is also used in prose and non fiction writing. The aims of this research are to find out the figurative language used in Kiss From a Rose song which is very popular in the era 90’s and sang by Seal and to analyze the contextual meaning of figurative language used in that song. This research used descriptive qualitative research method. The theory used in this research is theory figurative language.